(untitled) (Research, Society and Development, 2022)
Exclusive breastfeeding is the best food for the newborn; and, when extended to 6 months, it is associated with adequate nutritional status, reduced infections, and lower mortality. Despite the nutritional and immunological superiority of breast milk, there are high rates of weaning due to several factors such as difficulties related to breastfeeding and lack of knowledge of the mother about the benefits of breast milk, among others. In this context, this study aimed to evaluate the scientific evidence about the factors associated with early weaning. This was an integrative literature review of articles published from 2016 to 2021 available in the BVS, PubMed and SciELO databases. Twelve studies were included, of which 25% were carried out in Brazil. The prevalence of early weaning ranged from 7% to 85.7%, with lower prevalences observed in Brazil. Main factors associated with early weaning were age and low educational level of the mother, cesarean delivery, use of pacifiers, return to work and maternal perception of low amount of milk, showing that both sociodemographic and obstetric factors as well as inherent to the mother’s knowledge directly influence the duration of exclusive breastfeeding. However, it is necessary to investigate behavioral variables and serious psychiatric illnesses to understand the real determinants of early weaning, enabling health professionals to develop actions focusing mainly on health education.